Effects of Corticosteroid Treatment on Mycophenolic Acid Exposure in Renal Transplant Patients—Results From the SAILOR Study - Nourbakhsh, Nima; Ekberg, Jana; Skov, Karin; Peters, Christian Daugaard; Øzbay, Aygen; Lindner, Per; Buus, Niels Henrik (Frontiers in Pharmacology, 2021)
Background: Mycophenolic acid (MPA) is a potent immunosuppressive agent used in solid organ transplantation. MPA exhibits large interindividual variation in dose-normalized plasma concentrations but is nevertheless usually prescribed as a fixed dose without use of therapeutic drug monitoring (TDM). Data on the effect of corticosteroid (CS) treatment on MPA concentrations during concomitant tacrolimus treatment remains sparse. Methods: Data is based on TDM of MPA area under the concentration curve (AUC) in 210 renal transplant recipients participating in the prospective, randomized, controlled, multi-center trial (SAILOR) where a steroid-free immunosuppressive regimen with mycophenolate mofetil (MMF) and low-dose tacrolimus was compared with a conventional prednisolone-based treatment regimen. Multilevel mixed-effects linear regression post-hoc analyses of MPA AUC was performed. Results: Median MPA AUC at baseline (within the first 2 weeks post-transplant) in patients taking 2 g MMF daily was 53 mg*h/L (IQR: 42 – 68 mg*h/L). Between-patient variation in MPA AUC was up to 5-fold on the same MMF dose. Patients in the steroid-free group had 12.5% lower (95% CI; 3.2% - 20.9%, p = 0.01) MPA AUC levels at baseline compared to the steroid treated group. After the first 2 weeks post-transplant there were no significant differences in MPA AUC between the groups with MPA AUC being 4.2% lower (95% CI: -4.8% - 12,5%, p = 0.35) in the steroid-free vs. standard treatment group in restricted analysis after multivariate adjustment for tacrolimus trough level, body weight, time after transplantation and MMF dose. MMF dose was positively correlated with MPA AUC (p < 0.001) whereas body weight was negatively correlated with MPA AUC (p < 0.001). MPA AUC was 0.4% (95% CI: 0.2 – 0.6%, p<0.001) lower per 1 kg increase in weight. Tacrolimus trough levels had no significant effect on MPA AUC. Conclusion: Immunosuppression with CS during concomitant tacrolimus treatment was shortly after transplantation associated with a significantly higher MPA exposure but the effect was small and not maintained during follow-up. Low body weight was associated with higher MPA exposure, which supports a potential for weight adjusted MMF dosing.